Research on the Conversion of α-Hydroxy Ketones into 1,2-Diketones and Subsequent Transformations - Liang, Hanbing; Liu, Hui; Jiang, Xuefeng (Synlett, 2016)
1,2-Diketone derivatives are valuable molecules which are widely applied in organic synthesis. In this account, we discuss our recent research progress on the construction of 1,2-diketone derivatives and their subsequent transformations, including the synthesis of ynediones, the dicarbonylation of indoles and the preparation of heterocyclic hemiketals from ynediones. In addition, mechanistic investigations on the dicarbonylation of α-hydroxy ketones are described and plausible mechanisms are proposed. Furthermore, the synthesis of 3(2H)-furanones and 3(2H)-thienones from ynediones are also described.1 Introduction2 A Copper-Catalyzed One-Pot Approach Toward Ynediones3 Copper-Catalyzed Aerobic Oxidative Dicarbonylation of Indoles4 Synthesis of Heterocyclic Hemiketals from Ynediones5 Conclusion
Keywords: dicarbonylation; ynediones; α-hydroxy ketones; furanone; thienone; indole